Practitioner responses to children and young people involved in forced marriage. (8th February 2022) - Tarr, Sukey; Gupta, Anna
Abstract: Forced marriage is recognised as a form of child abuse in the UK. Despite evidence that this is a growing problem, there is little current research concerning the responses of child protection practitioners. This article is based on a study that explored the views and experiences of a range of practitioners who had been involved with safeguarding children with respect to forced marriage. Ten semi‐structured interviews were carried out, followed by two focus groups (n = 13); these explored the challenges and best practice related to working with children at risk of or in forced marriage situations. The findings highlighted the complex nature of the work and the particular vulnerability of children affected by forced marriage. The study found that practitioners struggled to respond effectively when guidance was unclear or when they had limited knowledge and experience of forced marriage. Effective practice was associated with a high standard of interagency work locally and with practitioners who had confidence and experience and were able to work proactively and assertively. Key Practitioner Messages: Effective practice responses to forced marriage require clearer national and local policy and guidance. Knowledgeable, confident and proactive staff enable good‐quality risk assessments and service responses. Practitioner training and development should include enhancing cultural competence and confidence when working with marginalised/BME families. Forced marriage is a nuanced, complex and diverse issue affected by high levels of vulnerability in children and young people.